Measuring corporate internationalisation: A review of measurement concepts and their use - Christoph Dörrenbächer (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
This paper discusses various ways of measuring corporate internationalisation. The concepts considered here became of crucial importance in the recent debate on globalisation, since many scholars link globalisation to a quantitative increase in the international activities of firms. However, this paper shows that opinions about the extent of this increase differ widely depending on what measurement concept is used. The paper further highlights that there is no unique and comprehensive measurement concept. Thus viable results depend on the difficult task of bringing research questions, measurement concepts and data availability into line. – – Dieses Papier befasst sich mit den in der Literatur vorgefundenen Konzepten zur Erfassung der Internationalisierung von Unternehmen. Diese Konzepte haben im Zuge der Globalisierungsdebatte eine besondere Bedeutung erlangt, da vermeintliche und tatsächliche Globalisierungsfolgen vielfach auf eine quantitative Zunahme der Internationalisierung von Unternehmen zurückgeführt werden. Diese Zunahme kann jedoch je nach Meßmethode erheblich variieren. Gezeigt wird, daß es weder ein einheitliches noch ein umfassendes Meßkonzept gibt und daß valide Aussagen nur durch eine gelungene Integration von Fragestellung, Meßkonzept und Datenverfügbarkeit zu erzielen sind.
Keywords: 330; Multinationales Unternehmen; Globalisierung; Wirtschaftsindikator; Welt